KOMUNIKASI PEMASARAN MENGGUNAKAN MEDIA SOSIALPADA RUMAH IDE COFFEE - Fauziah Nur Hutauruk; Agry Erickman (SUAN PUBLISHER, 2025)
Ineffective use of social media will make it difficult for Rumah Ide Coffee to compete in reaching its target market and may be abandoned by consumers. This study aims to determine the extent to which social media use brings benefits in marketing communications. The research method used is descriptive qualitative. The collected data will be presented through descriptive qualitative analysis to reveal aspects related to social media use at Rumah Ide Coffee in Medan City. The results of this study show that the function and role of social media as a mediator in marketing communications have been carried out by implementing an information strategy by looking at important points, namely paying attention to message patterns, delivery media, and managing message delivery. This research is expected to contribute to business owners who have their own admins as social media managers to be more effective in using their platforms by being more active in posting more interesting photos or videos on various existing social media